Students’ Strategies in Overcoming English Vocabulary Translation Difficulties at SMK Pelayaran Lintas Nusantara Barru - Syamsinar; Murni Mahmud; Maemuna Muhayyang (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study examined various strategies employed by maritime vocational students in overcoming challenges in translating English vocabulary, particularly in the context of maritime English. This issue is highly relevant given the important role of technical English in the maritime industry. Using a descriptive qualitative design and case study method, data were obtained through semi-structured interviews, classroom observations, and documentation. The research participants included 14 eleventh-grade students from the Nautical Department at SMK Pelayaran Lintas Nusantara Barru, who were selected through purposive sampling based on their active participation in English language learning.The research findings identified three dominant types of strategies: cognitive, metacognitive, and socio-affective. Cognitive strategies included the use of tools such as digital dictionaries and deriving meaning from context. Metacognitive strategies were evident in the students' ability to reflect on and adjust their approach after realizing translation errors. Socio-affective strategies, on the other hand, involved interacting with peers or teachers to overcome difficulties. These results indicated that students used deliberate and reflective learning methods, going beyond basic memorization, demonstrating proactive engagement in vocabulary acquisition.This study highlights the importance of integrating vocabulary learning strategies into vocational English teaching. From a theoretical perspective, these findings reinforce and extend the strategic learning models developed by Oxford (1990) and Schmitt (1997). Practically, these results provided useful guidance for language teachers in designing student-centered and context-based teaching approaches. Future research may consider exploring similar strategies in digital learning environments or among students in other vocational fields.